Metaphor matters - Andersen, Mette Skovgaard (HERMES - Journal of Language and Communication in Business, 2000)
The present article is intended as a contribution to the discussion of one of the most neg-lected themes in metaphor-research, i.e. the translation of metaphors in LSP-texts. It reports a pair of corpus space analyses, which were conducted as part of my Ph.D.-the-sis about translators’ metaphor-competence. The article takes as its starting-point the notion of context-dependent identification criteria in abstract themes such as business cycles and ends with the suggestion that we as researchers of translation should perhaps approach the problem from a more cotext-oriented point of view.